Sputum eosinophilia and the short term response to inhaled mometasone in chronic obstructive pulmonary disease. Issue 3 (1st March 2005) - Brightling, C E; McKenna, S; Hargadon, B; Birring, S; Green, R; Siva, R; Berry, M; Parker, D; Monteiro, W; Pavord, I D; Bradding, P
Abstract : Background: An association between the sputum eosinophil count and the response to a 2 week course of prednisolone has previously been reported in patients with chronic obstructive pulmonary disease (COPD). Whether the response to inhaled corticosteroids is related to the presence of eosinophilic inflammation is unclear. Methods: A randomised, double blind, crossover trial of placebo and mometasone furoate (800 μg/day), each given for 6 weeks with a 4 week washout period, was performed in subjects with COPD treated with bronchodilator therapy only. Spirometric tests, symptom scores, chronic respiratory disease questionnaire (CRQ), and induced sputum were performed before and after each treatment phase. Results: Ninety five patients were recruited of which 60 were randomised. Overall there were no treatment associated changes in forced expiratory volume in 1 second (FEV1 ), total CRQ, or sputum characteristics. After stratification into tertiles by baseline eosinophil count, the net improvement in post-bronchodilator FEV1 increased with mometasone compared with placebo progressively from the least to the most eosinophilic tertile. The mean change in post-bronchodilator FEV1 with mometasone compared with placebo in the highest tertile was 0.11 l (95% CI 0.03 to 0.19). This improvement was not associated with a fall in the sputum eosinophil count. Conclusions: An increased sputum eosinophil count is related to an improvement in post-bronchodilator FEV1 following treatment with inhaled mometasone in COPD, but the improvement is not associated with a reduction in the sputum eosinophil count.